2023
DOI: 10.1007/s00265-022-03287-2
|View full text |Cite
|
Sign up to set email alerts
|

Biologically meaningful moonlight measures and their application in ecological research

Abstract: Light availability is one of the key drivers of animal activity, and moonlight is the brightest source of natural light at night. Moon phase is commonly used but, while convenient, it can be a poor proxy for lunar illumination on the ground. While the moon phase remains effectively constant within a night, actual moonlight intensity is affected by multiple factors such as disc brightness, position of the moon, distance to the moon, angle of incidence, and cloud cover. A moonlight illumination model is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…Average illuminated per cent of the moon (AIPM, representing moon phase) on the night of fledging and an incident moon illumination index (IMII) at the time of fledging (i.e. the final read at the burrow) were calculated by the package moonlit (see electronic supplementary material for details) [24]. AIPM at peak fledge date was plotted to assess consistency among years.…”
Section: Methodsmentioning
confidence: 99%
“…Average illuminated per cent of the moon (AIPM, representing moon phase) on the night of fledging and an incident moon illumination index (IMII) at the time of fledging (i.e. the final read at the burrow) were calculated by the package moonlit (see electronic supplementary material for details) [24]. AIPM at peak fledge date was plotted to assess consistency among years.…”
Section: Methodsmentioning
confidence: 99%
“…Cozzi et al 2012 ; Peeva et al 2022 ). We used an alternative approach to obtain moonlight intensity on the ground based on the position of the moon, the brightness of the moon’s face, and several physical properties of light propagation, which is the proper measure of the amount of moonlight of real ecological importance (Śmielak 2023 ). Martens detect prey visually, thus increased moonlight levels may help them hunt, as is the case for other nocturnal mammals (Prugh and Golden 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the influence of moonlight on mammals’ activity is analysed by the lunar cycle (Cozzi et al 2012 ; Peeva et al 2022 ; Prugh and Golden 2014 ). This approach, however, does not take the amount of on-the-ground illumination throughout each night into account (Śmielak 2023 ). In our study, we used a new approach that combines the position of the moon in the sky, the brightness of the moon’s face and several physical properties of light propagation to count predicted moonlight illumination, relative to an ‘average’ full moon, for a given place and time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed above, natural night conditions range four orders of magnitude from starlight/new Moon of approximately 0.0006 lx to the full Moon directly overhead at approximately 0.2 lx [21]. Starlight conditions, due to the new Moon phase or the Moon being below the horizon, comprise approximately 50% of night-time hours, and thus, represent the most common night-time light condition [45]. Seymoure et al [12] translated the 2016 New world atlas of artificial night sky brightness [43] to illuminance experienced on the Earth's surface due to light pollution and found that approximately 23% of terrestrial habitats never experience new Moon lighting conditions and approximately 5% are ten times brighter and experience perpetual crescent Moon illumination.…”
Section: Alan Alters and Destroys Natural Light Cycles Responsible Fo...mentioning
confidence: 99%